2013
DOI: 10.4995/wrs.2013.1197
|View full text |Cite
|
Sign up to set email alerts
|

Meat quality of rabbits reared with two different feeding strategies: with or without fresh alfalfa ad libitum

Abstract: The aim of this study was to evaluate production performance, carcass characteristics and nutritive value of meat of rabbits reared under the 2 prevailing feeding strategies in Uruguay. One week after weaning, 96 purebred V line rabbits were randomly distributed between 2 treatments: (T1) commercial pelleted food ad libitum and (T2) commercial pelleted food ad libitum plus fresh alfalfa ad libitum. Each treatment included 12 cages containing 4 individuals each (2 males and 2 females). Growth performance charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 21 publications
3
14
4
1
Order By: Relevance
“…In addition, although the total meat cut yield did not differ between market categories, the only differences were found in fore leg (11.3 vs. 10.8%; P<0.01) and coccyx (0.8 vs. 0.7%; P<0.01) when medium and heavy-size carcasses were compared. Overall, the proportion of different carcass parts are in agreement with earlier studies (Pla et al, 1996;Ortiz-Hernandez and Rubio-Lozano, 2001;Hernandez et al, 2006;Capra et al, 2013;Dalle Zotte et al, 2015;Szendrő et al, 2016) and confirm previous findings when carcasses of different size were compared (Szendrő et al, 1998).…”
Section: Conversion Factors From Carcass To Edible Lean Meatsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, although the total meat cut yield did not differ between market categories, the only differences were found in fore leg (11.3 vs. 10.8%; P<0.01) and coccyx (0.8 vs. 0.7%; P<0.01) when medium and heavy-size carcasses were compared. Overall, the proportion of different carcass parts are in agreement with earlier studies (Pla et al, 1996;Ortiz-Hernandez and Rubio-Lozano, 2001;Hernandez et al, 2006;Capra et al, 2013;Dalle Zotte et al, 2015;Szendrő et al, 2016) and confirm previous findings when carcasses of different size were compared (Szendrő et al, 1998).…”
Section: Conversion Factors From Carcass To Edible Lean Meatsupporting
confidence: 82%
“…In past decades, some studies were conducted to estimate meat yields in order to evaluate the influence of genetic and environmental factors on carcass traits in rabbits (Pla et al, 1996;Ortiz-Hernandez and Rubio-Lozano, 2001;Hernandez et al, 2006;Capra et al, 2013;Dalle Zotte et al, 2015;Szendrő et al, 2016). In this context, no specific studies have been conducted to establish a conversion factor for determining edible yield of different categories of rabbit meat carcasses that are available in the market.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found in the literature. Capra et al (2013) fed a pelleted diet with or without fresh alfalfa ad libitum, Morales et al (2009) added 10, 20 or 30% green barley forage to the pelleted diet and they found decreased weight gain The results from feeding forages could depend on the forages nutritive value and their form (fresh or dried, given as pellets plus forage or mixed into the pellets).…”
Section: Effect Of Hay Supplementationmentioning
confidence: 96%
“…Scientists tested several forages for rabbits: alfalfa (Bianchi et al, 2006;Linga and Lukefahr, 2000;Capra et al, 2013), cassava foliage hay (Scapinello et al, 2000), Guinea grass and Verano stylo hays (Bamikole and Ezenwa, 1999), sulla hay (Kadi et al, 2011), whole maize plants (Martínez et al, 2006), green barley (Morales et al, 2009). The results of the experiments in which forages were not mixed as a balanced pelleted diet showed low productive performance (Carabaño and Fraga, 1991).…”
Section: Introductionmentioning
confidence: 95%
“…Scientists have tested several forages: dehydrated alfalfa on carcass traits and meat quality (Bianchi, Petracci, & Cavani, 2006), fresh alfalfa on carcass traits and fatty acid (FA) profile (Capra et al, 2013), or on FA profile (Dal Bosco et al, 2014), and green barley on dressing out percentage (Morales, Fuente, Juárez, & Ávila, 2009).…”
Section: Introductionmentioning
confidence: 99%